The Effect of STEM-PjBL Based Science and Social Learning on Critical Thinking and Collaboration Skills of Students of SD Negeri 3 Plumbungan - Putrianasari, Desi; Purwandari, Ristiana Dyah (Proceedings Series on Social Sciences & Humanities, 2024)
Students should be given the opportunity to be actively involved in learning, for them to be able to construct their knowledge through critical thinking and developing collaboration by working together. Through STEM-PjBL-based Science and Social learning, students are involved in contextual learning and students are encouraged to learn to explore all their abilities. This study aims to determine the effect of STEM-PjBL-based Science and Social learning on critical thinking and collaboration skills of grade 6 students of SD Negeri 3 Plumbungan for the academic year 2022/2023. This research was conducted at SD Negeri 3 Plumbungan, Pagentan District, Banjarnegara Regency. This study uses a quantitative research approach, with associative research types (relationships), and uses quantitative analysis methods (numerical data). Data on critical thinking and collaborative thinking skills were collected through observation using assessment instruments in the form of rubrics. 6 students are used as the sample in this study. The research data were processed using a simple linear regression test with results for the effect of STEM-PjBL-based Science and Social learning on critical thinking skills tcount = 3,600 and ttable = 2,776, meaning tcount > ttable. For the effect of STEM-PjBL-based science learning on collaboration skills, tcount = 3.331 and ttabel = 2.776, means tcount > ttable. Based on the results of this study, it shows that there is an influence of STEM-PjBL-based Science and Social learning on critical thinking and collaboration skills of grade 6 students of SD Negeri 3 Plumbungan for the academic year 2022/2023. This research provides insight into the importance of STEM-PjBL-based Science and Social learning to improve 21st century skills, especially critical thinking, and collaboration of learners.